Identification of active compounds in Vernonia anthelmintica (L.) willd by targeted metabolome MRM and kaempferol promotes HaCaT cell proliferation and reduces oxidative stress - Hu, Wen; Wang, Hongjuan; Li, Kaixiao; Lei, Zixian; Xiang, Fang; Li, Jun; Kang, Xiaojing (Frontiers in Pharmacology, 2024)
Vernonia anthelmintica (L.) Willd. is a traditional treatment for vitiligo in Xinjiang.However, its therapeutic mechanism remains unclear owing to its complex composition and limited research on its chemical profile. Methods: We employed a targeted metabolome approach, combining selective reaction monitoring/multiple response monitoring (SRM/MRM) with highperformance liquid chromatography and MRM mass spectrometry to quantitatively analyze the flavonoid constituents of V. anthelmintica. We also used network pharmacology and molecular docking to identify potential vitiligo-linked compounds and targets of V. anthelmintica seeds.Additionally, we assessed HaCaT cell proliferation by AAPH-induced, alongside changes in SOD activity and MDA content, following treatment with V. anthelmintica components. Finally, flow cytometry was used to detect apoptosis and ROS levels. Results and Discussion: We identified 36 flavonoid compounds in V. anthelmintica seeds, with 14 compounds exhibiting druggability. AKT1, VEGFA, ESR1, PTGS2, and IL2 have been identified as key therapeutic target genes, with PI3K/AKT signaling being an important pathway. Notably, kaempferol, one of the identified compounds, exhibited high expression in network pharmacology analysis. Kaempferol exhibited a strong binding affinity to important targets. Further, kaempferol enhanced HaCaT cell viability, inhibited apoptosis, reduced MDA levels, suppressed ROS activity, and upregulated SOD activity, increase the expression of cellular antioxidant genes, including HO-1, GCLC, GCLM, Nrf2, NQO1 and Keap1, providing significant protection against oxidative stress damage in vitro. Here, we present the first comprehensive study integrating SRM/MRM approaches and network analysis to identify active flavonoid compounds within V. anthelmintica (L.) Willd. Moreover, we revealed that its active ingredient, kaempferol, offers protection against AAPH-induced damage in keratinocytes, highlighting its potential as a clinical resource.